PEWARNAAN BATIK TULIS MENGGUNAKAN PEWARNA ALAMI DAN BAHAN FIKSASI KITOSAN PADA KELOMPOK BATIK TULIS ASIH MATAHARI KOTA BLITAR - Dina Kartika; Siti Tjahjani; Nita Kusumawati (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
Development on batik production processes inovation including dyeing process and pattern design become one of important factors that increase selling and production. Blitar city has unique batik product namely koi fish batik. The product is less popular among others batik from different city, so training on dyeing process with natural dye are essential to do. The objective of the training were to improve skill of dyeing process. The training for batik tulis group partner which Asih Matahari group included introduction of natural dye for batik dyeing and introduction of eco friendly fixation agent for dyeing process and use of padder tools to improve efficiency of dye coating process. The result of the training showed that batik group can use natural dye and do the dyeing with fixation agent Chitosan . Response of the training member showed high enthusiasm and interested toward training..